Closed circuit? Flow, influence and the liquid management of learning and skills. Issue 4 (4th July 2017) - Beighton, Christian
ABSTRACT: A new discourse is being deployed by the English learning and skills sector's new professional body, the Education and Training Foundation (ETF). This discourse repositions learning within a specific vision of corporate expectations. With a focus on deregulation in the sector and employer engagement, this repositioning deploys the terminology and mindset of a particular type of industrial process. This repositioning involves an important change, replacing a culture of micro-management with more decentralised techniques of control following changes at the national level of policy and beyond. Here, learning is analogous to the management of liquid, a move which is naturalised in texts which present education as an unavoidable and unassailable process or closed circuit of flow. Paul Virilio's work on the effects of speed is used to pinpoint ambivalence and incipient nihilism as central to this shift, critiquing the ETF's claims to represent the sector.